Computational Investigation of Effects of Side-Injection Geometry on Thrust-Vectoring Performance in a Fuel-Injected Dual Throat Nozzle - M. R. Salimi; R. Askari; M. Hasani (Journal of Applied Fluid Mechanics, 2022)
Dual-throat Nozzle (DTN) is known as one of the most effective approaches of fluidic thrust-vectoring. It is gradually flourishing into a promising technology to implement supersonic and hypersonic thrust-vector control in aircrafts. The main objective of the present study is numerical investigation of the effects of secondary injection geometry on the performance of a fuel-injected planar dual throat thrust-vectoring nozzle. The main contributions of the study is to consider slot and circular geometries as injector cross-sections for injecting four different fuels; moreover, the impact of center-to-center distance of injection holes for circular injector is examined. Three-dimensional compressible reacting simulations have been conducted in order to resolve the flowfield in a dual throat nozzle with pressure ratio of 4.0. Favre-averaged momentum, energy and species equations are solved along with the standard  k- ε model for the turbulence closure, and the eddy dissipation model (EDM) for the combustion modelling. Second-order upwind numerical scheme is employed to discretize and solve governing equations. Different assessment parameters such as discharge coefficient, thrust ratio, thrust-vector angle and thrust-vectoring efficiency are invoked to analyze the nozzle performance. Computationally predicted data are agreed well with experimental measurements of previous studies. Results reveal that a maximum vector angle of 17.1 degrees is achieved via slot injection of methane fuel at a secondary injection rate equal to 9% of primary flow rate. Slot injection is performing better in terms of discharge coefficient, thrust-vector angle and thrust-vectoring efficiency, whereas circular injection provides higher thrust ratio. At 2% secondary injection for methane fuel, vector angle and vectoring efficiency obtained by slot injector is 8% and 34% higher than the circular injector, respectively. Findings suggest that light fuels offer higher thrust ratio, vector angle and vectoring efficiency, while heavy fuels have better discharge coefficient. Increasing center-to-center distance of injector holes improves thrust ratio, while having a negative effect on discharge coefficient, vector angle and vectoring efficiency. A comparison between fuel injectant of current study and inert injectant in the previous studies indicates that fuel reaction could exhibit substantial positive effects on vectoring performance. Secondary-to-primary momentum flux ratio is found to play a crucial role in nozzle performance.